A bipolar plate for a flow battery and a method of making the same, the flow battery
Patent Information
- Application Number
- CN202610931771.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-06-25
AI Technical Summary
[0003]现有的液流电池普遍采用的柔性石墨双极板,但这种材料本身存在固有的、难以克服的物理缺陷:在电堆长期装配预紧力与运行温度的共同作用下,石墨会发生显著的蠕变松弛
[0019]本申请引入了可主动触发的形状恢复机制。当监测到压力衰减或定期维护时,通过加热使SMA功能层发生逆相变,可主动、周期性地将双极板恢复至初始平整状态,从而将电堆的界面接触压力“重置”回初始设计值。这从本质上将密封压力的变化曲线从“单调下降”转变为“可控恢复”,实现了对电堆密封可靠性的主动管理与终身维护。
Smart Images

Figure CN122599463B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, and more particularly to a bipolar plate for a flow battery and a method for preparing the same, which is a flow battery. Background Technology
[0002] Bipolar plates are one of the core components of flow battery stacks, and their performance directly affects the energy efficiency, power density, and lifespan of flow batteries.
[0003] Existing flow batteries commonly use flexible graphite bipolar plates, but this material itself has inherent and difficult-to-overcome physical defects: under the combined effects of long-term assembly preload and operating temperature, graphite undergoes significant creep relaxation. This is an irreversible microscopic slippage and structural compaction process, leading to plastic thinning in the thickness direction of the bipolar plate. Macroscopically, this manifests as a continuous decrease in contact pressure between components within the stack over time. Experimental data shows that after 500 hours of testing under simulated operating conditions, the pressure retention rate of traditional graphite bipolar plates can drop to about 70%, meaning a pressure decrease of nearly 30%.
[0004] More seriously, once traditional graphite bipolar plates undergo plastic deformation (such as warping caused by assembly overload, accidental impact, or localized thermal stress), the damage is irreversible. This means that the sealing and electrical contact performance of the fuel cell stack will continue to deteriorate until electrolyte leakage or a sharp increase in internal resistance occurs, ultimately forcing the stack to be shut down and disassembled before the damaged components can be replaced. This passive maintenance mode of "damage equals scrap" is not only costly to maintain but also results in huge downtime losses, making it one of the key bottlenecks restricting the large-scale commercial application of flow batteries.
[0005] Therefore, an improved bipolar plate for flow batteries is needed. Summary of the Invention
[0006] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of the claims.
[0007] In one aspect, this application provides a bipolar plate for a flow battery, the bipolar plate comprising two graphite plates and a nickel-titanium-based shape memory alloy plate disposed between the graphite plates; The nickel-titanium-based shape memory alloy plate is made of nickel-titanium-based shape memory alloy, which is composed of Ni x Ti y M z This indicates that M is one or more metallic elements selected from copper, niobium, vanadium, iron, and chromium; x, y, and z represent the atomic percentages of each element, with 45.0% ≤ x ≤ 52.0%, 40.0% ≤ y ≤ 47.0%, and 1.0% ≤ z ≤ 15.0%, and the sum of x, y, and z is 100%. The austenitic phase transformation end temperature of the nickel-titanium based shape memory alloy is 60℃-100℃.
[0008] In one exemplary embodiment, the nickel-titanium-based shape memory alloy has an austenitic phase transformation end temperature (A) in the range of 80°C ± 5°C. f It also has an austenitic phase transformation initiation temperature within the range of 50℃±5℃ (A s Nickel-titanium-copper alloy.
[0009] In an exemplary embodiment, the nickel-titanium-based shape memory alloy is a nickel-titanium-niobium alloy having an austenitic phase transformation end temperature in the range of 90℃±5℃ and an austenitic phase transformation start temperature in the range of 60℃±5℃.
[0010] In one exemplary embodiment, the thickness of the nickel-titanium-based shape memory alloy plate is 0.05-0.2 mm.
[0011] In one exemplary embodiment, the thickness of the graphite plate is 0.5-2.0 mm.
[0012] In another aspect, this application provides a method for preparing the above-mentioned bipolar plate, comprising the following steps: 1) Pre-treat the nickel-titanium-based shape memory alloy plate; 2) Pre-treat two graphite plates; 3) Two graphite plates are bonded to the nickel-titanium shape memory alloy plate using a conductive adhesive film and then rolled into a composite plate; and 4) The composite plate is hot-pressed and cooled to obtain the bipolar plate.
[0013] In one exemplary embodiment, in step 1), the nickel-titanium-based shape memory alloy plate is sanded to a matte finish using sandpaper, ultrasonically cleaned with ethanol, and then dried and cooled; and / or, In step 2), the surfaces of the two graphite plates to be joined are treated with sandpaper, ultrasonically cleaned with ethanol, and then dried and cooled.
[0014] In an exemplary embodiment, in steps 1) and 2), the sandpaper is 200-800 grit; and / or, The ultrasonic washing time is 10 min to 60 min; and / or, The drying temperature is 40~60℃, and the drying time is 10min~60min.
[0015] In an exemplary embodiment, in step 4), the hot pressing includes placing the composite plate in a preheated hot press, the preheating temperature of which is 40°C to 100°C.
[0016] In one exemplary embodiment, in step 4), the cooling includes reducing the temperature to less than 60°C and the pressure to 1.0~2.0 MPa.
[0017] In another aspect, this application provides a flow battery including the bipolar plate described above or a bipolar plate manufactured by the method described above.
[0018] In another aspect, this application provides the application of nickel-titanium-based shape memory alloys in the fabrication of bipolar plates for flow batteries, wherein the nickel-titanium-based shape memory alloy is made of Ni x Ti y M z This indicates that M is one or more metallic elements selected from copper, niobium, vanadium, iron, and chromium; x, y, and z represent the atomic percentages of each element, with 45.0% ≤ x ≤ 52.0%, 40.0% ≤ y ≤ 47.0%, and 1.0% ≤ z ≤ 15.0%, and the sum of x, y, and z is 100%. The austenitic phase transformation end temperature of the nickel-titanium based shape memory alloy is 60℃~100℃; During the use of the bipolar plate, it is periodically heated to a temperature higher than the end temperature of the austenite phase transformation.
[0019] This application introduces an actively triggered shape recovery mechanism. When pressure decay is detected or periodic maintenance is required, heating causes an inverse phase transition in the SMA functional layer, actively and periodically restoring the bipolar plates to their initial flat state, thereby "resetting" the interfacial contact pressure of the fuel cell stack back to its initial design value. This essentially transforms the sealing pressure change curve from "monotonically decreasing" to "controllable recovery," enabling proactive management and lifetime maintenance of the fuel cell stack's sealing reliability.
[0020] This application transforms a bipolar plate from a consumable item that is rendered unusable upon damage into a smart component capable of active repair by introducing a shape memory alloy (SMA) functional layer with shape memory effect. This application achieves this by controlling the inverse phase transformation end temperature (austenite phase transformation end temperature A) of the SMA layer. f The design is set above the battery's maximum operating temperature, ensuring the alloy plate remains stably in a martensitic or martensitic-austenitic mixed state during normal battery operation (e.g., within a temperature range below 40°C). When repair is required, external heating is used to raise the temperature to A. f The above triggers the reverse phase transition, causing the alloy layer of the bipolar plate to actively recover to its preset flat shape.
[0021] This application introduces a shape memory alloy (SMA) functional layer with shape memory effect, enabling the bipolar plate to achieve periodic performance recovery and giving the bipolar plate a reusable repair capability.
[0022] This application combines the chemical stability of graphite with the metallic toughness and large deformation recovery capability of SMA. This composite structure can absorb significant mechanical shocks and assembly stresses, preventing brittle cracking, and can be repaired by heating after overload deformation. This significantly improves the production yield of bipolar plates, the assembly reliability of the fuel cell stack, and its tolerance to complex operating conditions.
[0023] This application utilizes a dense SMA interlayer, exhibiting corrosion resistance superior to conventional graphite materials. The alloy layer is not only a functional layer but also a superior barrier that is electrochemically more stable and inert. Even if the outer graphite layer suffers localized damage, this SMA barrier, with its lower corrosion tendency and rate, can effectively prevent electrolyte penetration and corrosion propagation in the long term. This significantly enhances the inherent safety margin and durability of the bipolar plate under extreme environments, providing robust protection for the fuel cell stack.
[0024] Other features and advantages of this application will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the application. Other advantages of this application may be realized and obtained by means of the methods described in the description. Attached Figure Description
[0025] The accompanying drawings are used to provide an understanding of the technical solutions of this application and constitute a part of the specification. They are used together with the embodiments of this application to explain the technical solutions of this application and do not constitute a limitation on the technical solutions of this application.
[0026] Figure 1 This is a schematic structural diagram of a bipolar plate provided according to an exemplary embodiment of this application. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application are described in detail below. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be arbitrarily combined with each other.
[0028] Example 1 This embodiment uses a commercially available pre-shaped nickel-titanium-copper shape memory alloy plate with a thickness of 0.1 mm and an austenitic phase transformation temperature range of A. s =50±5℃, A f =80℃±5℃, the alloy foil has undergone stress relief treatment by the manufacturer and can be directly surface processed.
[0029] The specific composition of the nickel-titanium-copper shape memory alloy plate is (atomic percentage at.%): Ni 49.2%, Ti 40.8%, Cu 10.0% (i.e., Ni 49.2 Ti 40.8 Cu 10 ).
[0030] The specific preparation steps are as follows: 1) Use 400-grit sandpaper to evenly polish the nickel-titanium-copper shape memory alloy plate until it is uniformly matte, sonicate with ethanol for 20 minutes, dry at 40℃ for 60 minutes, and cool before use.
[0031] 2) Use 400-grit sandpaper to polish the surface of the graphite plate to be bonded, clean it with ethanol by ultrasonic cleaning for 20 minutes, dry it at 40℃ for 40 minutes, and cool it for later use.
[0032] 3) Apply a low-temperature conductive adhesive film (commonly used in this field or commercially available) to the bonding surface of the first and second graphite plates, then symmetrically attach the two graphite plates to both sides of the nickel-titanium-copper shape memory alloy plate, and roll them with rollers to remove air bubbles and align them.
[0033] 4) Check the overall alignment, place it in a vacuum hot press at 45℃ / 8MPa for 60 minutes, and allow it to cool naturally.
[0034] Furthermore, flow channels can be configured on the bipolar plate using methods commonly used in this field.
[0035] Example 2: This embodiment uses a commercially available pre-shaped nickel-titanium-niobium shape memory alloy plate with a thickness of 0.1 mm and an austenitic phase transformation temperature range of A. s =60℃±5℃, A f =90℃±5℃, this alloy foil has undergone stress relief treatment by the manufacturer and can be directly surface-processed. The specific composition of the nickel-titanium-niobium shape memory alloy plate is (atomic percentage at.%): Ni 47.0%, Ti 44.0%, Nb 9.0% (Ni 47 Ti 44 Nb9).
[0036] 1) Use 400-grit sandpaper to uniformly polish the nickel-titanium-niobium shape memory alloy plate until it is uniformly matte, sonicate with ethanol for 20 minutes, dry at 40℃ for 60 minutes, and cool before use.
[0037] 2) Use 400-grit sandpaper to polish the surface of the graphite plate to be bonded, clean it with ethanol by ultrasonic cleaning for 20 minutes, dry it at 40℃ for 40 minutes, and cool it for later use.
[0038] 3) Apply a low-temperature conductive adhesive film (commonly used in this field or commercially available) to the bonding surface of the first and second graphite plates, then symmetrically attach the two graphite plates to both sides of the nickel-titanium-niobium shape memory alloy plate, and roll them with rollers to remove air bubbles and align them.
[0039] 4) Check the overall alignment, place it in a vacuum hot press at 50℃ / 8MPa for 60 minutes, and allow it to cool naturally.
[0040] Furthermore, flow channels can be configured on the bipolar plate using methods commonly used in this field.
[0041] Performance testing: Performance tests were performed on the bipolar plates of Examples 1 and 2, as well as on conventional graphite bipolar plates, including: Contact resistance: The contact resistance of the bipolar plate was tested according to NB / T-42007-2013; Bending strength; Corrosion current density; Creep resistance: Refer to the contact pressure and durability test in GB / T-20042, including: Step 1 (simulated creep): Assemble the sample with carbon felt, apply a pressure of 1.5 MPa, and keep it in a 40℃ oven for 500 h; Step 2 (test attenuation): Test the residual pressure; Step 3 (low temperature repair): Place the entire assembly in a constant temperature environment above Af temperature for 1 h, and cool to room temperature; Step 4 (measure recovery): Measure the contact pressure again.
[0042] The test results are shown in Table 1 below.
[0043] Table 1 As can be seen from the results in Table 1, the bipolar plates of Embodiments 1 and 2, which contain the specific SAM functional layer of this application, are significantly better than the conventional graphite bipolar plate of Comparative Example 1 in terms of key indicators such as contact resistance (reduced by about 20%) and mechanical toughness (fracture deflection increased by nearly 300%).
[0044] In the same creep test, the pressure decay of traditional graphite bipolar plates is irreversible; however, the bipolar plates of Embodiments 1 and 2 of this application, after detecting pressure decay, can restore the contact pressure due to creep decay to more than 98% of the initial value through a single heating repair. By periodically repeating the above process, this application makes the sealing performance of the fuel cell stack no longer a monotonically decreasing curve, but a curve that can be restored in a stepwise manner through active intervention. This upgrades the maintenance mode of fuel cell stack components from "replacement after damage" to "early intervention and proactive maintenance," and fundamentally avoids equipment downtime and safety accidents caused by sealing failure, providing unprecedented protection for the long-term safe operation of the fuel cell stack.
[0045] While the embodiments disclosed in this application are as described above, the content is merely for the purpose of facilitating understanding of this application and is not intended to limit this application. Any person skilled in the art to which this application pertains may make any modifications and changes in the form and details of the implementation without departing from the spirit and scope disclosed in this application; however, the scope of protection of this application shall still be determined by the scope defined in the appended claims.
Claims
1. A bipolar plate for a flow battery, characterized in that, The bipolar plate includes two graphite plates and a nickel-titanium-based shape memory alloy plate placed between the graphite plates; The nickel-titanium-based shape memory alloy plate is made of nickel-titanium-based shape memory alloy, which is composed of Ni x Ti y M z This indicates that M is one or more metallic elements selected from copper, niobium, vanadium, iron, and chromium; x, y, and z represent the atomic percentages of each element, with 45.0% ≤ x ≤ 52.0%, 40.0% ≤ y ≤ 47.0%, and 1% ≤ z ≤ 15.0%, and the sum of x, y, and z is 100%. The austenitic phase transformation end temperature of the nickel-titanium based shape memory alloy is 60℃-100℃.
2. The bipolar plate according to claim 1, characterized in that, The nickel-titanium-based shape memory alloy is a nickel-titanium copper alloy having an austenitic transformation end temperature in the range of 80℃±5℃ and an austenitic transformation start temperature in the range of 50℃±5℃; or, The nickel-titanium-based shape memory alloy is a nickel-titanium-niobium alloy with an austenitic phase transformation end temperature in the range of 90℃±5℃ and an austenitic phase transformation start temperature in the range of 60℃±5℃.
3. The bipolar plate according to claim 1 or 2, characterized in that, The thickness of the nickel-titanium-based shape memory alloy plate is 0.05-0.2 mm; and / or, The thickness of the graphite plate is 0.5-2.0 mm.
4. A method for preparing a bipolar plate according to any one of claims 1-3, characterized in that, Includes the following steps: 1) Pre-treat the nickel-titanium-based shape memory alloy plate; 2) Pre-treat two graphite plates; 3) Two graphite plates are bonded to the nickel-titanium-based shape memory alloy plate using a conductive adhesive film and then rolled into a composite plate; and 4) The composite plate is hot-pressed and cooled to obtain the bipolar plate.
5. The method according to claim 4, characterized in that, In step 1), the nickel-titanium-based shape memory alloy plate is sanded to a matte finish, ultrasonically cleaned with ethanol, and then dried and cooled; and / or, In step 2), the surfaces of the two graphite plates to be joined are treated with sandpaper, ultrasonically cleaned with ethanol, and then dried and cooled.
6. The method according to claim 5, characterized in that, In steps 1) and 2), the sandpaper is 200-800 grit; and / or, The ultrasonic cleaning time is 10 min to 60 min; and / or, The drying temperature is 40~60℃, and the drying time is 10min~60min.
7. The method according to claim 4, characterized in that, In step 4), the hot pressing includes placing the composite plate in a preheated hot press, wherein the preheating temperature of the hot press is 40℃~100℃.
8. The method according to claim 4, characterized in that, In step 4), the cooling includes reducing the temperature to less than 60°C and the pressure to 1.0~2.0 MPa.
9. A flow battery, characterized in that, Includes the bipolar plate according to any one of claims 1-3 or the bipolar plate manufactured by any one of claims 4-8.
Citation Information
Patent Citations
Coated substrate and product including the same and methods of making and using the same
CN103490074A
Composite molding process of bipolar plate of multilayer flow battery
CN120978107A